2023
DOI: 10.1101/2023.03.07.531551
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Concussion-related disruptions to hub connectivity in the default mode network are related to symptoms and cognition

Abstract: Concussions present with a myriad of symptomatic and cognitive concerns; however, the relationship between these functional disruptions and the underlying changes in the brain are not yet well understood. Hubs, or brain regions that are connected to many different functional networks, may be specifically disrupted after concussion. Given the implications in concussion research, we quantified hub disruption within the default mode network (DMN) and between the DMN and other brain networks. We collected resting-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
(171 reference statements)
1
3
0
Order By: Relevance
“…Greater magnitudes of information flow (stronger connectivity) in the concussed group compared to the control group align with numerous reports of increased functional connectivity in the acute phase of concussion (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The significantly higher magnitudes of information flow are suggestive of hyperconnectivity, indicating that the concussed female youth brain exerts more effort at rest compared to a healthy, uninjured brain.…”
Section: ) Increased Magnitude Of Information Flowsupporting
confidence: 83%
See 1 more Smart Citation
“…Greater magnitudes of information flow (stronger connectivity) in the concussed group compared to the control group align with numerous reports of increased functional connectivity in the acute phase of concussion (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The significantly higher magnitudes of information flow are suggestive of hyperconnectivity, indicating that the concussed female youth brain exerts more effort at rest compared to a healthy, uninjured brain.…”
Section: ) Increased Magnitude Of Information Flowsupporting
confidence: 83%
“…The DMN is a network of cerebral regions that show coordinated activity during wakeful rest and is associated with self-referential emotions and mind-wandering thoughts (8). Although not entirely undisputed, it is commonly reported that the acute phase after injury has increased functional connectivity (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Reduced anterior connectivity paired with increased posterior connectivity has also been commonly reported (20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the adverse outcomes related to concussion history can be viewed through the lens of network neuroscience. In fact, concussion is increasingly being considered as an injury characterized by disruptions to structural and functional brain connectivity (41)(42)(43)(44)(45). These network disruptions have been linked with many of the behavioral outcomes of concussion history including cognitive impairment (46)(47)(48), emotion disruptions including depression (49)(50)(51), and changes in motor function (52).…”
Section: Introductionmentioning
confidence: 99%
“…Concussion awareness has increased considerably over the last decade particularly in sports-related brain injuries (Snyder and Giza 2019). Altered brain connectivity is a signature of concussion injuries both in the acute and in the chronic epochs (Hayes, Bigler et al 2016, Bouchard, Higgins et al 2023, Onicas, Deighton et al 2023). Broadly, these studies report decrements in structural (diffusion magnetic resonance imaging (MRI)) and functional (evoked or resting state MRI) connectivity between affective, motor and somatic brain regions.…”
Section: Introductionmentioning
confidence: 99%